Primary otomycosis: Assessment of risk factors and identification of fungal agents – A tertiary care hospital experience - Philip Ganeesh Moorthy R; Praveena VG; Sowmya AV (Asian Journal of Medical Sciences, 2023)
Background: Primary otomycosis is one of the common conditions seen in general clinical practices. Although non-fatal, inappropriate management of this condition may lead to serious complications. Aims and Objectives: A cross-sectional study was conducted in our tertiary care hospital to determine the fungal agents in primary otomycosis and its associated risk factors. Materials and Methods: A total of 62 consecutive patients of more than 18 years of age with clinical diagnosis of otomycosis were included in this study. Samples were collected and processed and the fungal isolate was identified. The predisposing factors, fungal isolate, and demographical profile of the patients were analyzed. Results: About 61.29% were males and 38.71% were females. Majority of the patients were in the age group of 18–30 years (62.90%). The most common associated risk factor was habitual self-cleaning (50%), followed by oil instillation (30.65%). Itching (75.81%) was the most common symptom followed by ear discharge (45.16%). About 79.03% of our fungal isolates were Aspergillus species, Aspergillus niger being the most common (58.06 %). About 12.90% of our isolates were Candida species. About 63.27% of Aspergillus isolates was associated with habitual self-cleaning and 62.50% of Candida isolates was isolated with the instillation of oil. About 66.67% of Penicillium species and 100% of Rhizopus species are associated with inappropriate use of topical antibiotics. Conclusion: Health education of the community along with knowledge of common fungal agents causing otomycosis and its associated risk factor will help in reducing the incidence of otomycosis, which along with proper management will prevent further complications.